Story-Wallah - Selvadurai, Shyam (New York : Houghton Mifflin Company, 2004)
Story-Wallah gathers the finest South Asian voices in fiction for the first time in a single volume. In this book, some of the world's best fiction writers hawk their wares from different parts of the South Asian diaspora - Sri Lanka, India, the United States, Great Britain, Guyana, Malaysia, Trinidad, Fiji - creating a virtual map of the world with their tales. These stories explore universal themes of identity, culture, and home, and Story-Wallah includes a rich array of experiences: a honeymoon in Sri Lanka, the trials of a Bangladeshi refugee in England, life on a sugar plantation in Trinidad, the attempts of an Indian family to arrange a marriage for their rebellious daughter
Bibliographies
English
Golam Newaz
Keywords: American fiction -- South Asian American authors; South Asia -- Social life and customs -- Fiction